Appraising workfare - Ravallion, Martin (1999)
Workfare programs aim to reduce poverty by providing low-wage work to those who need it. They are often turned to in a crisis. This article offers some simple analytical tools that can be used to rapidly appraise the cost-effectiveness of an existing workfare operation as a basis for deciding whether the program should be expanded. For pedagogic purposes, two stylized versions of a range of programs found in practice are analyzed: one for a middle-income country, the other for a low-income country. The cost of a given gain to the poor is about the same for both programs, although the components of that cost are very different, with implications for the timing of benefits. The author points to program design changes that could enhance the impact on poverty. - Reproduced
Keywords: Poverty - India; Work experience programmes - India; Poverty